ChemInform Abstract: Synthesis of 3‐Acylindoles by Visible‐Light Induced Intramolecular Oxidative Cyclization of o‐Alkynylated N, N‐Dialkylamines. Issue 50 (16th December 2014) - Zhang, Ping; Xiao, Tiebo; Xiong, Shengwei; Dong, Xichang; Zhou, Lei
Abstract The reaction can be scaled up.